1990
DOI: 10.1111/j.1365-2044.1990.tb14455.x
|View full text |Cite
|
Sign up to set email alerts
|

Acid aspiration prophylaxis in 288 obstetric anaesthetic departments in the United Kingdom

Abstract: Summary The choice of drugs for acid aspiration prophylaxis in 288 obstetric anaesthetic departments in the United Kingdom was determined by questionnaire. The results are compared with a similar survey of anaesthetic departments 5 years ago. The prescription of sodium citrate and the H2 receptor antagonist ranitidine has superseded that of Mist, magnesium trisilicate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 20 publications
1
10
0
2
Order By: Relevance
“…[8][9][10] This survey confirms that 97% of UK units are using ranitidine as the drug of choice (Table 2), although dosage intervals vary widely from 4-hourly to 24-hourly ( Table 3). The most common dosage route and interval is orally 6-hourly as seen in 62% of the units using ranitidine.…”
Section: Discussionsupporting
confidence: 75%
“…[8][9][10] This survey confirms that 97% of UK units are using ranitidine as the drug of choice (Table 2), although dosage intervals vary widely from 4-hourly to 24-hourly ( Table 3). The most common dosage route and interval is orally 6-hourly as seen in 62% of the units using ranitidine.…”
Section: Discussionsupporting
confidence: 75%
“…30 This approach is consistent with reports from the UK between 1984 and 1993. 26,27,29 We found high use of ranitidine and sodium citrate in the elective situation, but only 64% of the category 1 caesarean section patients (arguably at highest risk of aspiration) received some form of prophylaxis. Possible explanations include the considerable time pressure of these cases, inadequate training and familiarity with general anaesthesia for caesarean section and the recognition that aspiration is a rare event.…”
Section: Discussionmentioning
confidence: 94%
“…[26][27][28][29][30][31][32] Aspiration prophylaxis for caesarean section is commonly recommended and the combination of sodium citrate, ranitidine and metoclopramide has been suggested. 24 Results from a New Zealand postal survey in 1998 showed that 95% of departments would recommend sodium citrate before emergency obstetric surgery, with 72% also including a histamine type-2 receptor antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Bemerkenswert ist allerdings, daß immerhin in 11,3% der Krankenhäuser vor der Intubation regelmäßig mit der Maske beatmet wurde. Daten zur Aspirationsprophylaxe zeigen im internationalen Vergleich eine sehr große Variationsbreite, wobei Natriumcitrat und Ranitidin allein oder in Kombination die favorisierten Medikamente sind [2,4,15,17,20,23].…”
Section: Allgemeinanästhesie Zur Csunclassified